Utilization of Nata De Durio as a Constipation Preventive (Preliminary Animal Studies) - SYAM, Tri Sutriani; Ika Yustisia; Syahrijuita Kadir; Huhammad Husni Cangara; Sartini (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Constipation is a symptom/problem that arises in the process of defecation, which is not smooth and irregular due to a lack of fiber intake in the body. Nata de durio is an extracellular cellulose made from durian seeds and formed from the activity of the bacterium Acetobacter xylinum, which contains high enough fiber so that it can regulate and maintain intestinal function in the defecation process. The purpose of this study is to assess the effect of using nata de durio as a natural fiber in the defecation process in vivo and to assess its effect on the transition time of feces in the small intestine of mice. The current study was an experimental study using male mice that were given distilled water as a negative control, inulin as a positive control, and nata seed de durio with doses of 0.02 gram, 0.04 gram, and 0.08 gram as a treatment group for 5 weeks. According to the findings of this study, the administration of nata de durio had a better effect on the amount of feces, weight of feces, frequency of defecation, and consistency of feces compared to the control group. The study's conclusion is that nata de durio can be used as a natural fiber in improving the defecation pattern of BALB/c male mice.